1998
DOI: 10.1590/s0100-879x1998000100004
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular ATP in the lymphohematopoietic system: P2Z purinoceptors and membrane permeabilization

Abstract: The effects of extracellular nucleosides and nucleotides on many organs and systems have been recognized for almost 50 years. The effects of extracellular ATP (ATP o ), UTP o , ADP o , and other agonists are mediated by P2 purinoceptors. One of the most dramatic effects of ATP o is the permeabilization of plasma membranes to low molecular mass solutes of up to 900 Da. This effect is evident in several cells of the lymphohematopoietic system and is supposed to be mediated by P2Z, an ATP 4--activated purinocepto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

5
42
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(47 citation statements)
references
References 37 publications
(58 reference statements)
5
42
0
Order By: Relevance
“…These channels were called Z pores and could only be recorded under cell-attached patch-clamping conditions. Because they carry currents of large cations (Tris, 121 Da and N-methyl-Dglucamine (NMDG), 195 Da) and anions (glutamate, 146 Da) we have proposed that they could be a pathway for dye uptake (CoutinhoSilva and Persechini, 1997;Persechini et al, 1998). We therefore investigated whether a similar large conductance non-selective channel could be detected in HEK-P2X 7 cells under cell-attached patch-clamping conditions.…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…These channels were called Z pores and could only be recorded under cell-attached patch-clamping conditions. Because they carry currents of large cations (Tris, 121 Da and N-methyl-Dglucamine (NMDG), 195 Da) and anions (glutamate, 146 Da) we have proposed that they could be a pathway for dye uptake (CoutinhoSilva and Persechini, 1997;Persechini et al, 1998). We therefore investigated whether a similar large conductance non-selective channel could be detected in HEK-P2X 7 cells under cell-attached patch-clamping conditions.…”
mentioning
confidence: 98%
“…Whole-cell patch-clamp recordings performed on cells transfected with P2X 7 receptors indicate a permeability shift from low to high M r molecules in the first seconds after stimulation by ATP e , while keeping the selectivity for cations (Virginio et al, 1999). In addition, although ATP e induces the uptake of both cationic and anionic dyes in macrophages (Steinberg et al, 1987a), the uptake of anions has not been reported either in HEK-293 cells or astrocytomas transfected with P2X 7 , neither has it been reported in lymphocytes (Wiley et al, 1993;Surprenant et al, 1996;Rassendren et al, 1997;Chessell et al, 1998;Ferrari et al, 2000;Paukert et al, 2002;Duan et al, 2003;Suadicani et al, 2006), suggesting that in these experimental situations, ATP e might not induce membrane permeabilization to anions.Based on cell-attached patch-clamping experiments demonstrating the opening of large cation-and anion-permeant channels (Z pores) induced by ATP e in macrophages, we have hypothesized that the permeabilization pore of macrophages could be distinct from the receptor itself, but coupled to P2X 7 through an unidentified signaling mechanism (Coutinho-Silva and Persechini, 1997;Persechini et al, 1998). This possibility has recently been corroborated by data showing that pannexin-1, a protein that forms large non-selective transmembrane channels (Barbe et al, 2006), is involved in the phenomenon of P2X 7 -associated, ATP e -induced membrane permeabilization (Pelegrin and Surprenant, 2006;Locovei et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In one view, the channel formed by P2X 7 receptor is gradually open upon activation, increasing its permeability from small molecules to large ones (up to 900 Da) (80,81). In the other, P2X 7 channel is formed upon activation, inducing the production or release of a second messenger that may autoactivate P2X 7 receptor or an independent pore-forming membrane protein (16,61). Recently, we have demonstrated that the action of second messengers is necessary to form the pore (28).…”
mentioning
confidence: 99%
“…The initial suggestions for dependency of cytoplasmic factors in this event were originated from electrophysiological data in outside or inside out configurations with no large conductance channel recordings (Coutinho-Silva & Persechini, 1997;Persechini et al, 1998;Petrou et al, 1997). Posteriorly, other groups have investigated the P2X7R pore formation induced by intracellular signaling and how mutated amino acids or truncated regions affect functional availability of the receptor.…”
Section: Intracellular Signalling Pathways Associated With Large Condmentioning
confidence: 99%